The elimination of trachoma as a public health problem in Mexico: From national health priority to national success story. - Víctor Quesada-Cubo; Dey Carol Damián-González; Francisco Gibert Prado-Velasco; Nadia Angélica Fernández-Santos; Gustavo Sánchez-Tejeda; Fabián Correa-Morales; Hermilo Domínguez-Zárate; Abel García-Orozco; Martha Idalí Saboyá-Díaz; María Jesús Sánchez-Martín (Public Library of Science (PLoS), 2022)
Introduction Mexico was the first country in the Americas and the third in the world to eliminate trachoma as a public health problem, as validated by the WHO in 2017. Objective To describe the critical elements that favored the elimination of trachoma as a public health problem in Mexico and the public health impact of this success. Methodology A revision and compilation of data and information contained in the dossier presented by the country to PAHO/WHO to obtain the validation of trachoma elimination as a public health problem was conducted by a group of delegates from the national and local trachoma prevention and control program. Data from the national and local surveillance systems and reports of actions conducted after achieving the elimination goal were also included. Critical elements that favored the achievement of the elimination goal from 1896 to 2019 were extracted. Results Mexico reached the elimination of trachoma in 2016 obtaining the validation in 2017. 264 communities were no longer endemic and 151,744 people were no longer at risk of visual impairment or possible blindness due to trachoma. The key to the success of this elimination process was primarily the local leadership of health authorities with sustained funding for brigades, increased access to potable water and sanitation, and key alliances with indigenous authorities, health authorities, and government institutions that contributed to the achievement of the goal. The SAFE strategy started implementation in Mexico in 2004 as a comprehensive package of interventions. SAFE stands for surgery, antibiotics, facial cleanliness, and improvement of the environmental conditions. These actions impacted drastically on the number of new cases trachmatous trichiasis (TT) and trachomatous inflammation-follicular (TF), which decreased from 1,794 in 2004 to zero in 2016. Conclusions The elimination of trachoma as a public health problem in Mexico is a true success story that may serve as a model example for the elimination of other neglected infectious diseases in the Americas.